Pengaruh Sosial Media Instagram Terhadap Keputusan Pembelian Pada Aisy Drink Kota Bima - Nurul Afrianti; Ismunandar Ismunandar (Universitas 45 Surabaya, 2023)
This research aims to determine the social media Instagram on purchasing decisions at Aisy Drink, Bima City. This type of research is associative. The research instrument used in this research was a questionnaire with a Likert scale. The population used in this research were all consumers who had seen or been exposed to Aisy drink product promotions via social media, with a sample size of 50 respondents. The data collection techniques used in this research were observation, questionnaires and literature study. The data analysis techniques used in this research are validity test, reliability test, classical assumption test, simple linear regression analysis, simple correlation coefficient, determination test, and t test. The research results show that social media Instagram influences purchasing decisions at Aisy Drink Bima City.